Health-related quality of life in elderly patients with advanced non-small cell lung cancer comparing carboplatin and weekly paclitaxel doublet chemotherapy with monotherapy. Issue 3 (23rd June 2016) - Fiteni, Frédéric; Anota, Amélie; Bonnetain, Franck; Oster, Jean-Philippe; Pichon, Eric; Wislez, Marie; Dauba, Jérôme; Debieuvre, Didier; Souquet, Pierre-Jean; Bigay-Game, Laurence; Molinier, Olivier; Dansin, Eric; et al.
In the Intergroupe Francophone de Cancérologie Thoracique 0501 trial the carboplatin-paclitaxel chemotherapy increased toxicity (most frequent, decreased neutrophil count, asthenia). We longitudinally compared health-related quality of life (HRQoL) of the two treatment arms. In total, 451 patients aged 70–89 years with advanced non-small cell lung cancer (NSCLC) were randomly assigned to receive carboplatin plus paclitaxel or vinorelbine or gemcitabine. HRQoL was assessed by means of the European Organisation for Research and Treatment of Cancer QLQ-C30 questionnaire at baseline, week 6 and week 18. Using a five-point decrease as the minimal clinically important difference, patients treated with the chemotherapy doublet exhibited a significant longer time until definitive deterioration (TUDD) for two HRQoL dimensions: physical functioning (median TUDD: 2.04 for the doublet versus 1.71 months for monotherapy; log-rank p=0.01) and nausea and vomiting (median: not reached versus 4.83, respectively; log-rank p=0.046). Cox multivariate analysis revealed the carboplatin and paclitaxel arm to be independently associated with longer TUDD for these two HRQoL dimensions. In addition, TUDD didn't significantly differ between the two arms for all the other HRQoL dimensions. The chemotherapy doublet did not reduce TUDD in elderly patients with advanced NSCLC. Moreover, TUDD was prolonged for two HRQoL dimensions, namely physical functioning and nausea and vomiting. Carboplatin plus paclitaxel chemotherapy does not reduce quality of life in elderly patients with advanced NSCLC http://ow.ly/obcW300xe59